2021
DOI: 10.1002/chem.202003386
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Strain‐Promoted Azide–Alkyne Cycloaddition in Polymer Chemistry

Abstract: Highly efficient reactions that enable the assembly of molecules into complex structures have driven extensive progress in synthetic chemistry. In particular, reactions that occur under mild conditions and in benign solvents, while producing no by‐products and rapidly reach completion are attracting significant attention. Amongst these, the strain‐promoted azide–alkyne cycloaddition, involving various cyclooctyne derivatives reacting with azide‐bearing molecules, has gained extensive popularity in organic synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 133 publications
0
28
0
Order By: Relevance
“…In recent years, 1 H -1,2,3-Triazoles are of increasing interest to researchers as one of the most promising classes of heterocyclic compounds for different purposes of bioconjugation [ 1 ] design of new catalysts [ 2 ], supramolecular ensembles [ 3 , 4 ], and polymeric materials [ 5 ]. 1,2,3-Triazoles are widely synthetically available compounds due to the development of simple and effective methods of their preparation on the base of “click” reaction of Cu-catalyzed azide–alkyne cycloaddition (CuAAC) [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 1 H -1,2,3-Triazoles are of increasing interest to researchers as one of the most promising classes of heterocyclic compounds for different purposes of bioconjugation [ 1 ] design of new catalysts [ 2 ], supramolecular ensembles [ 3 , 4 ], and polymeric materials [ 5 ]. 1,2,3-Triazoles are widely synthetically available compounds due to the development of simple and effective methods of their preparation on the base of “click” reaction of Cu-catalyzed azide–alkyne cycloaddition (CuAAC) [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study on the in vitro drug release showed enhanced drug release at an acidic pH value in comparison to a neutral pH value. Importantly, the amount of DOX required for MCF-7 cells was decreased after the support of DOX molecules on the polymer prodrug, which resulted in reduced side effects ( Scheme 18b ) [ 48 49 ].…”
Section: Reviewmentioning
confidence: 99%
“…Alkynes are synthetically important moieties that can further be transformed into many functionalized molecules. [63][64] Therefore, the development of improved methods for the synthesis of alkynes is essential in organic chemistry. 65 For the first time, in 2016, Cheng and coworkers reported a method for decarboxylative alkynylation of carboxylic acids 12 using organo-photocatalyst (Figure 6).…”
Section: Figurementioning
confidence: 99%